2004
DOI: 10.1248/bpb.27.1784
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Deep Seawater and Surface Seawater in the Preventive Effect of Atherosclerosis

Abstract: Seawater has been used for thalassotherapy and atopic dermatitis for a long time in medical treatment. However, there are still many obscure points in the scientific evidence about the effective of medical treatment.Deep seawater at depths between about 500 m and 1000 m circulates around the world. 1) Deep seawater is known to have such characteristics as being clean and rich in mineral components compared to surface seawater, [2][3][4] and application has been attempted in many fields. [5][6][7][8][9][10][11]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 25 publications
5
64
0
2
Order By: Relevance
“…9,23) Yoshikawa et al 3) demonstrated that deep-sea water inhibited the accumulation of lipid and permeation of macrophages in the arterial wall in rabbits fed 1% cholesterol for 4 weeks. Miyamura et al 4) also reported that among rabbits fed 1% cholesterol for 12 weeks, there was less LDL cholesterol in plasma and less cholesterol accumulated in the arterial wall in the deep-sea water group than in the control group. They proposed as a possible anti-atherosclerotic mechanism that the activity of glutathione peroxidase, an antioxidative enzyme, increased due to the administration of deep-sea water and that Ca and Mg suppressed the absorption of cholesterol in the small intestine.…”
Section: Effects Of Deep-sea Water On Hypercholesterolemia and Atheromentioning
confidence: 94%
See 2 more Smart Citations
“…9,23) Yoshikawa et al 3) demonstrated that deep-sea water inhibited the accumulation of lipid and permeation of macrophages in the arterial wall in rabbits fed 1% cholesterol for 4 weeks. Miyamura et al 4) also reported that among rabbits fed 1% cholesterol for 12 weeks, there was less LDL cholesterol in plasma and less cholesterol accumulated in the arterial wall in the deep-sea water group than in the control group. They proposed as a possible anti-atherosclerotic mechanism that the activity of glutathione peroxidase, an antioxidative enzyme, increased due to the administration of deep-sea water and that Ca and Mg suppressed the absorption of cholesterol in the small intestine.…”
Section: Effects Of Deep-sea Water On Hypercholesterolemia and Atheromentioning
confidence: 94%
“…Deepsea water improved mineral imbalances and atopic eczema/ dermatitis syndrome in humans 2) and was effective in the prevention of hyperlipidemia and atherosclerosis in cholesterol-fed rabbits. 3,4) We expect that the continuous intake of deep-sea water could prevent hypertension as well as hypercholesterolemia, because investigators have revealed that oral supplementation of calcium 5,6) or magnesium 7,8) to hypertensive patients lowered blood pressure in addition to reducing the serum total cholesterol level. 7) Hypercholesterolemia and hypertension occur due to genetic as well as dietary factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12) Pharmacological effects have been reported, such as improvement in cases of atopic dermatitis 13) and fatigue, 14,15) suppression of bowel diseases including duodenal ulcer, 16) and suppression of breast cancer metastasis. 17) Our group has also found that deep sea water is effective for improving dyslipidemia and arteriosclerosis, 18,19) which suggests deep sea water's utility as a stimulator of antioxidant system in the body. However, as there are many sources of deep sea water even in Japan alone, and commercially available deep sea waters differ in hardness and production methods, we consider it necessary to characterize their respective mineral compositions to distinguish the functionality of each type of water.…”
mentioning
confidence: 98%
“…해양심층수는 청정성과 양질의 미네 랄 함유 때문에 우리나라를 포함하여 미국, 일본, 노르웨이 등에 서 식품, 의료, 농업, 환경, 수산 분야에 사용하고 있으며, 표층수 와 심해의 온도차를 이용한 열에너지 자원으로도 개발되고 있다 (Joo, 2011;. 수심 350 m의 해양심층수는 동물의 blood LDL cholesterol 수치를 감소시키고, 혈액순환을 개선하 는데 효과가 있다고 보고되었다 (Miyamura et al, 2004;Katsuda et al, 2008).…”
unclassified